The container transport system during Covid-19: An analysis through the prism of complex networks. (January 2022) - Guerrero, David; Letrouit, Lucie; Pais-Montes, Carlos
Abstract: This paper analyses the changes on the maritime network before and after the Covid-19 outbreak. Using a large sample of vessel movements between ports, we show a decrease in the global maritime connectivity and significant differences between ports and inter-port links. Furthermore, we find that Covid-19 mitigation measures implemented by governments affected regional port hierarchies differently, with a reduction in port concentration in Europe and Africa and an increase in Asia and North America. Globally, very large ports and small but densely inter-connected ones resisted better to the crisis than the others, while small transshipment hubs and bridges appear to have been more negatively impacted. These findings have implications for the design of more resilient port strategies and transport policies by states and firms. Highlights: Global container transport is analyzed as a complex network of ports. A net decrease in connectivity is observed between 2019 and 2020. Emerging inter-port links are identified. Covid-19 mitigation measures have impacted regional port hierarchies differently. Large ports and small but densely inter-connected ports resisted better.